On entire solutions of certain type of nonlinear differential equations - Zhang, Fengrong; Wu, Linlin; Yang, Jing; Lü, Weiran (AIMS mathematics, 2020)
In this paper, we shall extend some results regarding the growth estimate of entire solutions of certain type of linear differential equations to that of nonlinear differential equations. Moreover, our results will include several known results for linear differential equations obtained earlier as special cases.